Pre-school teachers’ beliefs towards early english language learning (ELL) among pre-schoolers in the east coast states of peninsular Malaysia - Aisyah Khaleeda, Rosli (2020)
Recent studies have shown that English is a global language that is widely used for various purposes. The number of non-native speakers of English outnumbering the number of the native speakers implies that English plays an important role in global communication and is a recognized passport for greater opportunities for education and employment. Furthermore, it also provides an opportunity for individuals to climb the social ladder, improve their socioeconomic status, develop career potential and improve their lifestyle over the long term. In many countries, especially in Malaysia, English is used for instructional purposes. In the learning of English, teachers play an important role in ensuring the proficiency of English language for second language learners. As many studies have made it apparent that pre-school children acquire languages efficiently at their age (Hartshorne et al., 2018; Lenneberg, 1967; Shafa, 2015), it is important for pre-school teachers to take this opportunity to teach English accordingly at this level. However, English is not one of the main requirements for a private pre-school teacher position, particularly in the three East Coast states of Peninsular Malaysia - Pahang, Terengganu and Kelantan. Thus, teachers’ beliefs indicate the importance of determining whether pre-school children will receive adequate English inputs at their age despite the drawback. This research aims to identify pre-school teachers’ beliefs in their ability to teach English to pre-schoolers and their beliefs in pre-schoolers' preparedness in learning English in the East Coast of Peninsular Malaysia. In this research, a set of questionnaires which consist of 29 items were distributed to 114 pre-school teachers in Pahang, Terengganu and Kelantan. Interview sessions were also conducted. The questionnaire showed a Cronbach alpha value of 0.88 and 0.89 respectively which show a high level of reliability in both sections of the questionnaire. The results of this research illustrate that the majority of the pre-school teachers held positive beliefs in the teaching of English to pre-schoolers but they were still having doubts in terms of pre-schoolers' preparedness. The findings of the research will contribute to the development of English syllabus for pre-schoolers in Malaysia and will eventually enhance the standard of English amongst children in Malaysia in the future.